Broadband Absorption Enhancement in Modified Grating Thin-Film Solar Cell - Muhammad H. Muhammad; Mohamed Farhat O. Hameed; Salah S. A. Obayya (IEEE Photonics Journal, 2017)
A novel design of a highly efficient modified grating thin-film solar cell (SC) is reported and analyzed using a 3-D finite difference time domain (3-D FDTD) method. The modified grating has side wings and is covered by 1-D silicon nanorods. The suggested grating has a great potential to harvest the light into the nanoscale active layer. Further, the light trapping through the suggested design is significantly enhanced by the photonic nanorods. The modified grating and nanorods produce an absorption enhancement in different parts of the solar spectrum. Furthermore, the nanorods are considered as a second grating to obtain multiple light trapping which increases the optical path length. Additionally, the nanorods can couple the incident light into the discrete modes of the active layer over an extended wavelength range. Therefore, a broadband absorption enhancement for the suggested SC is achieved. The effects of the structure geometrical parameters on the absorption, ultimate efficiency, and short circuit current of the proposed design are investigated. The performance of the reported SC using crystalline silicon, hydrogenated amorphous silicon, and gallium arsenide is also studied. The numerical results show that high efficiency of 43.114% can be achieved using gallium arsenide with short circuit current density of 35.27 mA/cm2.